2015
DOI: 10.21774/ing.v9i26.589
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades hidrodinámicas de la fibra dietaría a partir de harina de cáscaras de naranja (Citrus sinensis) y mango (Mangifera indica L)

Abstract: En este estudio se determinaron diversas propiedades fisicoquímicas e hidrodinámicas para la fibra obtenida a partir de cáscaras de naranja y mango, con el fin de conocer características de su capacidad de absorción, la cual se expresa como la cantidad máxima de retener agua o aceite por gramo del material seco de cada una de las muestras evaluadas. Para determinar las propiedades hidrodinámicas de las muestras se necesitó el epicarpio de dichas frutas totalmente seco y molido. El contenido de fibra fue evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…The influence of temperature increase in techno-functional properties of peach palm peel flour is due to the thermal excitation of molecules which causes an increase in absorption properties. This is probably caused by protein dissociation in the presence of water molecules that join polar remains of polypeptide chains (Kumar et al., 2019; Martínez-Girón et al., 2015; Vergara-Valencia et al., 2007). In addition, the dietary fiber also increases these properties when suffering dissociation due to the effect of temperature (Elleuch et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of temperature increase in techno-functional properties of peach palm peel flour is due to the thermal excitation of molecules which causes an increase in absorption properties. This is probably caused by protein dissociation in the presence of water molecules that join polar remains of polypeptide chains (Kumar et al., 2019; Martínez-Girón et al., 2015; Vergara-Valencia et al., 2007). In addition, the dietary fiber also increases these properties when suffering dissociation due to the effect of temperature (Elleuch et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A literature review showed no evidence of studies about the effect of particle size and temperature on techno-functional properties of peach palm peel ( Bactris gasipaes ) in Colombia (Martínez-Girón et al., 2017; Ordóñez-Santos et al., 2016; Pinzón-Zárate et al., 2015). However, other authors had evaluated the effect of temperature on techno-functional properties of by-product flours of other fruits (Hincapié et al., 2014; Martínez-Girón et al., 2015). For instance, a study on the effect of temperature on functional properties of mango peel flour, with treatments at 40 °C to 60 °C showed that temperatures of 55 °C produces desirable values of swelling capacity (7.75 mL/g), water retention capacity (4.95 g/g), and oil retention capacity (1.45 g/g) (Hincapié et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Con relación al porcentaje de extracto etéreo y carbohidratos, Garbanzo et al (2012) reportaron un valor de porcentaje de grasa de 13 % y un porcentaje de carbohidratos de 67 % en harina de mesocarpio de chontaduro, lo cual es un valor muy similar al obtenido en este estudio. De acuerdo con estos resultados, se evidencia que la harina de residuos de chontaduro es un producto con un alto nivel lipídico, posiblemente por su alto contenido de ácidos grasos poliinsaturados, si se compara con la harina de epicarpio de otras frutas que presentan un bajo valor de extracto etéreo -por ejemplo, la harina de epicarpio de mango y naranja, que presentan un porcentaje de grasa de 1,84 % y 1,73 % respectivamente, de acuerdo a lo informado por Martínez, Díaz, & Martínez (2015)-.…”
Section: Determinación De Actividad Antioxidante (% Dpph)unclassified
“…Con el fin de satisfacer esta demanda se han realizado numerosas investigaciones tendientes a encontrar las tecnologías que permitan obtener un mayor aprovechamiento de las fuentes existentes (Boye et al, 2010;Jaimes, Acevedo & Severiche, 2015;Martínez, Díaz, & Martínez, 2015).…”
Section: Introductionunclassified